Zambia : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report, 2004)
This paper reviews Zambia's First Poverty Reduction Strategy Paper (PRSP) Implementation Progress Report covering January 2002-June 2003. The report describes the first one and half years of the implementation of the PRSP in four strategic areas, namely economic and social sectors, governance, infrastructure, and crosscutting issues. It covers the macroeconomic performance-budget and structural reforms with regard to the PRSP refined indicators. The report focuses on the progress made in undertaking structural reforms to support the policy and institutional changes required to effectively implement the PRSP.